The role of ecotypic variation in driving worldwide colonization by a cosmopolitan plant. Issue 1 (24th January 2018) - Neuffer, Barbara; Wesse, Christina; Voss, Ingo; Scheibe, Renate
Abstract : Short-living plants meet their main energy demand by photosynthesis of rosette leaves. These leaves optimize their yield as required for successful growth in so many different locations around the world. Do they cope with varying conditions by one general-purpose genotype and phenotypic plasticity or by ecotypic differentiation with a specific genetic background? How did leaves of a plant like Shepherd's Purse, a weed colonizing all continents and climatic regions during a time period of only 500 years, evolve? We demonstrate that a combination of physiological, anatomical and morphological differentiation might allow such tremendous colonization success. Abstract: For almost 100 years now, ecotypic differentiation of plant species has been a major topic of research. In changing environments, the question needs to be answered as to how long it takes to adapt, and which parameters are subject to this fast adaptation. Short-living colonizing plant species are excellent examples, especially when they are selfing. Shepherd's Purse Capsella bursa-pastoris (Brassicaceae) is one of the most wide-spread flowering species on earth and avoids only the hot and humid tropics. Many studies demonstrated the ecotypic differentiation of C. bursa-pastoris in various regions of the world but ecotypic differentiation regarding adaptability of anatomy and physiology of rosette leaves so far remained less recognized. However, the leaves are relevant for subsequent seed set; in particular, winter-annual accessions require a robust rosette to survive adverse conditions. Leaf-related traits such as the thickness of the mesophyll and epidermis, stomatal density, photosynthetic capacity and the ability to withstand and even use high light conditions were therefore analysed in provenances from various climatic zones. Photosynthetic capacity depends on leaf anatomy and cellular physiological parameters. In particular, the ability to dynamically adjust the photosynthetic capacity to changing environmental conditions results in higher fitness. Here, we attempt to relate these results to the four Mendelian leaf types according to Shull.